ETC L2 Fluxnet (half-hourly) from Hyltemossa - Michal Heliasz; Natascha Kljun; Tobias Biermann; Jutta Holst; Thomas Holst; Peter Kornacher; Maj-Lena Linderson; Meelis Molder; Janne Rinne (Integrated Carbon Observation System, 2025)
Half-hourly Fluxes and Meteo measurements processed with the standard FLUXNET procedure used for the FLUXNET2015 collection (ONEFlux suite).
Heliasz, M., Kljun, N., Biermann, T., Holst, J., Holst, T., Kornacher, P., Linderson, M., Molder, M., Rinne, J. (2025). ETC L2 Fluxnet (half-hourly) from Hyltemossa, 2017-12-31–2025-09-30, ICOS RI, https://hdl.handle.net/11676/6biHeYoi_0jROCWry5eS-3Ja
Keywords: Ecosystem Thematic Centre; ICOS; time instant, UTC; time instant, UTC; time instant, local non-DST time; time instant, local non-DST time; air temperature; air temperature; incoming shortwave radiation; incoming shortwave radiation; latent heat flux; latent heat flux; sensible heat flux; sensible heat flux; net ecosystem exchange; net ecosystem exchange; vapour pressure deficit; vapour pressure deficit; ecosystem respiration; ecosystem respiration; gross primary CO2 production; gross primary CO2 production; quality flag (int); quality flag (int); incoming long-wave radiation, net radiometer; incoming long-wave radiation, net radiometer; quality flag; quality flag; precipitation (total); precipitation (total); atmospheric pressure; atmospheric pressure; wind speed; wind speed; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap